Hungarian Monitoring, 2 June 1989 . [Magyar rádiófigyelő], 1989. június 2 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - How much does military spending cost the USSR? - The Hungarian Parliament as seen by Czechoslovak eyes - Free Speech Forum in Warsaw Domestic Affairs: - Parliament: modifying this year's budget; Miklós Németh's report on suspension of Gabčíkovo-Nagymaros construction - Briefing between government and EKA - István Bibó memorial conference on finding the third way - Festive Book Week opens this year in Sopron, Károly Grósz gives opening speech Economy: - South Korea intends to extend USD 250 million bank credit to Hungary Külpolitika: - Mennyibe kerül a SZU-nak a katonai költségvetés? - A magyar Parlament csehszlovák szemmel - Szabad Szónoklatok Fóruma Varsóban Belpolitika: - Országgyűlés: az idei költségvetés módosítása; Németh Miklós beszámolója a bős-nagymarosi építkezés felfüggesztéséről - Tájékozódó megbeszélés a kormány és az EKA között - Bibó István emlékkonferencián a harmadik út kereséséről - Az idén Sopronban nyitották meg az Ünnepi Könyvhetet, amelyen Grósz Károly mondott ünnepi beszédet Gazdaság: - Dél-Korea 250-millió dollár értékű bankhitelt szándékozik Magyarországnak nyújtani